The Collaborative Role of Parents and Teachers in Implementing Inclusive Education at MI Nurul Falahiyah - Asma’ Ashila Yumna; Muhammad Fauzan Muttaqin (Examinations: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Inclusive education is an educational approach that ensures the fulfillment of every student’s right to learn without discrimination, including children with special needs. The successful implementation of inclusive education at the primary education level is strongly influenced by effective collaboration between teachers and parents. This study aims to describe the collaborative roles of parents and teachers in the implementation of inclusive education at MI Nurul Falahiyah. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The research subjects consisted of classroom teachers and parents of students. The findings indicate that parent–teacher collaboration is manifested through continuous communication, parental involvement in school activities, and cooperation in supporting students’ academic and social development. Such collaboration contributes positively to the creation of an inclusive, conducive, and responsive learning environment that meets students’ diverse needs. Therefore, synergy between parents and teachers is a crucial factor in supporting the successful implementation of inclusive education at MI Nurul Falahiyah.